2023
DOI: 10.1002/fft2.218
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alginate lyase treatment on structural characteristics and anti‐photoaging activity of alginate from Sargassum fusiforme

Abstract: An alginate (named P1) prepared from Sargassum fusiforme has been proven to have significant anti‐photoaging activity in our previous study. In this study, alginate lyase was used to obtain P1 hydrolysates with different molecular weights, and their structural characteristics and anti‐photoaging activity were compared. Results showed that alginate lyases could rapidly degrade the molecular weight of P1 and slightly changed its chemical composition. Fourier transform infrared spectra indicated that alginate lya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Current studies have shown that the degradation methods of acid, high-temperature, enzyme, or free radical could effectively decrease the molecular weight (M W ) of polysaccharides [2]. Moreover, degradation of polysaccharides usually has a significant effect on biological activity [3][4][5]. For example, ascorbic acid combined with H 2 O 2 -degraded polysaccharides from Lycium barbarum L. leaves increased the gastrointestinal transport and bioaccessibility of endogenous minerals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have shown that the degradation methods of acid, high-temperature, enzyme, or free radical could effectively decrease the molecular weight (M W ) of polysaccharides [2]. Moreover, degradation of polysaccharides usually has a significant effect on biological activity [3][4][5]. For example, ascorbic acid combined with H 2 O 2 -degraded polysaccharides from Lycium barbarum L. leaves increased the gastrointestinal transport and bioaccessibility of endogenous minerals [6].…”
Section: Introductionmentioning
confidence: 99%
“…[16] Many studies found that alginate had anti-photoaging activity. [17] Hu et al found that an alginate-purified fraction (named P1), prepared from Sargassum fusiforme, showed strong anti-photoaging activity. P1 could reduce collagen, oxidative stress, and inflammation response in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Many studies found that alginate had anti‐photoaging activity. [ 17 ] Hu et al. found that an alginate‐purified fraction (named P1), prepared from Sargassum fusiforme , showed strong anti‐photoaging activity.…”
Section: Introductionmentioning
confidence: 99%